PENGARUH MODEL PEMBELAJARAN PROBLEM BASED INSTRUCTION DISERTAI MEDIA AUDIO VISUAL TERHADAP HASIL BELAJAR BIOLOGISISWA KELAS X SMA NEGERI 1 SOLOK SELATAN TAHUN AJARAN 2025/2026 - Yulia Ratna Sari; Yoko Masnarivan (Jurnal Genta Mulia, 2026)
This research aims to find out the effect of Problem Based Instruction learning model with audiovisual media in biology learning on the learning achievement of the X graders of SMA Negeri 1 South Solok in the school year of 2025/2026. This study was a quasi-experimental research with quantitative approach. The research design used was posttest only control design with the experiment group applying Problem Based Instruction with audiovisual media and control group applying discussion, lecture, debriefing, presentation methods. The population of research was all X graders of SMA Negeri 1 South Solok in the school year of 2025/2026. The sampling technique used was cluster random sampling. The sample of research consisted of X3 grade containing 35 students as the experiment group and X6 grade containing 35 students as control group. Techniquesof collecting data usedwere questionnaire, test,observation, anddocumentation. The hypothesis testing was done using t-test. This research concluded that the Problem Based Instruction with audiovisual media affected significantly the biology learning achievement of the X graders of SMA Negeri 1 South Solok in the school year of 2025/2026 in cognitive, affective, and psychomotor domains.